SPE/IADC Drilling Conference and Exhibition 2011
DOI: 10.2118/139830-ms
|View full text |Cite
|
Sign up to set email alerts
|

Axial Excitation as a Means of Stick Slip Mitigation - Small Scale Rig Testing and Full Scale Field Testing

Abstract: This paper describes the work carried out at NOV Downhole on an in house designed and built, small scale, vibration test rig which was developed with the purpose of replicating stick slip and studying various stick slip mitigation methods.There are currently well established down hole tools that offer improvements axial friction reduction and axial load transfer by way of introducing axial excitation into the drill string -with resulting improvements in ROP and MSE.As a result, such tools also have the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Forster 105 studied the mitigation of stick-slip vibration by introducing axial excitations into the drillstring. For this purpose, laboratory tests were conducted at the National Oilwell Varco Downhole Ltd. on small-scale vibration test apparatus designed to reproduce the stick-slip phenomenon and test different stick-slip reduction methods (Figure 20).…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Forster 105 studied the mitigation of stick-slip vibration by introducing axial excitations into the drillstring. For this purpose, laboratory tests were conducted at the National Oilwell Varco Downhole Ltd. on small-scale vibration test apparatus designed to reproduce the stick-slip phenomenon and test different stick-slip reduction methods (Figure 20).…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…4 for the model including AST). Besides, both torques are governed by a similar set-valued force law, see (15) and (25). As a consequence, it is not possible to distinguish between the wearflat torque and the set-valued frictional torque below the AST in numerical simulations with the model.…”
Section: Drilling Performance Variablesmentioning
confidence: 99%
“…However, the dynamics of the drill-string, the bitrock interaction and the (frictional) contact along the drill-string in a deviated well are not taken into account in this modelling approach. A different approach for ROP improvement is the selection of drill-string components, such as drill-bits or down-hole tools located at the BHA of the drill-string [4,5,15]. Down-hole tools can be either active [5,15] or passive [4,31,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuators were used to apply the numerically predicted displacement at the interface of bit and BHA to simulate deep downhole conditions. Forster (2011) demonstrated that axial excitations help in reducing stick-slip oscillations. An experimental rig was designed by Cheng et al (2011) to investigate dynamic behavior of BHA.…”
Section: Previous Studiesmentioning
confidence: 99%